A randomized trial examining the effects of Conjoint Behavioral Consultation in rural schools: Student outcomes and the mediating role of the teacher–parent relationship. (April 2017) - Sheridan, Susan M.; Witte, Amanda L.; Holmes, Shannon R.; Coutts, Michael J.; Dent, Amy L.; Kunz, Gina M.; Wu, ChaoRong
Abstract: The results of a large-scale randomized controlled trial of Conjoint Behavioral Consultation (CBC) on student outcomes and teacher–parent relationships in rural schools are presented. CBC is an indirect service delivery model that addresses concerns shared by teachers and parents about students. In the present study, the intervention was aimed at promoting positive school-related social-behavioral skills and strengthening teacher–parent relationships in rural schools. Participants were 267 students in grades K-3, their parents, and 152 teachers in 45 Midwest rural schools. Results revealed that, on average, improvement among students whose parents and teachers experienced CBC significantly outpaced that of control students in their teacher-reported school problems and observational measures of their inappropriate (off-task and motor activity) and appropriate (on-task and social interactions) classroom behavior. In addition, teacher responses indicated significantly different rates of improvement in their relationship with parents in favor of the CBC group. Finally, the teacher–parent relationship was found to partially mediate effects of CBC on several student outcomes. Unique contributions of this study, implications of findings for rural students, study limitations and suggestions for future research are discussed.